Dynamic regulation of membrane integrity to enhance l‐malate stress tolerance in Candida glabrata. Issue 11 (31st July 2021) - Liang, Guangjie; Zhou, Pei; Lu, Jiaxin; Liu, Hui; Qi, Yanli; Gao, Cong; Guo, Liang; Hu, Guipeng; Chen, Xiulai; Liu, Liming
Abstract: Microbial cell factories provide a sustainable and economical way to produce chemicals from renewable feedstocks. However, the accumulation of targeted chemicals can reduce the robustness of the industrial strains and affect the production performance. Here, the physiological functions of Mediator tail subunit Cg Med16 at l ‐malate stress were investigated. Deletion of Cg Med16 decreased the survival, biomass, and half‐maximal inhibitory concentration (IC50 ) by 40.4%, 34.0%, and 30.6%, respectively, at 25 g/L l ‐malate stress. Transcriptome analysis showed that this growth defect was attributable to changes in the expression of genes involved in lipid metabolism. In addition, tolerance transcription factors Cg USV1 and Cg YAP3 were found to interact with Cg Med16 to regulate sterol biosynthesis and glycerophospholipid metabolism, respectively, ultimately endowing strains with excellent membrane integrity to resist l ‐malate stress. Furthermore, a dynamic tolerance system (DTS) was constructed based on Cg USV1, Cg YAP3, and an l ‐malate‐driven promoter Pcgr‐10 to improve the robustness and productive capacity of Candida glabrata . As a result, the biomass, survival, and membrane integrity of C. glabrata 012 (with DTS) increased by 22.6%, 31.3%, and 53.8%, respectively, compared with those of strain 011 (without DTS). Therefore, at shake‐flask scale, strain 012 accumulated 35.5 g/L l ‐malate, and the titer and productivity of l ‐malate increased by 32.5% and 32.1%, respectively, compared with those of strain 011 . This study provides a novel strategy for the rational design and construction of DTS for dynamically enhancing the robustness of industrial strains. Abstract : Microbial cell factories provide a sustainable and economical way to produce chemicals. However, the accumulation of targeted chemicals can reduce the robustness of the industrial strains and affect the production performance. In this study, a DTS strategy was proposed which can improve the robustness and productive capacity of C. glabrata to L‐malate. And the DTS enhances the robustness of C. glabrata by dynamically regulating of membrane integrity, thereby increasing the production capacity for L‐malate.